Assessment of Heavy Metal Concentration in Commercially Important Fishes From Cross River System Itu, Nigeria - Isangedighi A. I,; Imaobong E. O,; Jacob U. S,; Andikan E. U, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The Cross River System provides critical economic and ecological services to people around its environment. However, human activities along the river make it a potential dumpsite for industrial, domestic, urban, and agricultural wastes. This research aimed to investigate the concentration of heavy metals in commercially important fish species from the Cross River System, Itu, Nigeria. Samples were collected monthly from June to September 2021. The concentration of heavy metals were analyzed using Atomic Absorption Spectroscopy (AAS) and the following order of increment was recorded Mn (29.467±0.04 mg/kg) > Cu (24.897±0.02 mg/kg) > Zn (18.190±0.00 mg/kg) > Fe (8.923±0.01 mg/kg) > Ni (0.065±0.00 mg/kg) > Cd (0.033±0.00 mg/kg) > Pb (0.030±0.00 mg/kg) > Cr (0.018±0.00 mg/kg). Similarly, the following order in decreased was also recorded Cr (0.011±0.00 mg/kg) < Pb (0.015±0.00 mg/kg) < Ni (0.015±0.01 mg/kg) < Cd (0.021±0.00 mg/kg) < Fe (7.62±0.52 mg/kg) < Zn (14.813±0.91 mg/kg) < Cu (20.133±0.03 mg/kg) < Mn (23.042±0.01 mg/kg) respectively. Monthly variation in heavy metals was also recorded. Chrysichthys Nigrodigitatus from Mbiabo Edere had the highest concentration of Zn, and Mn (18.00±1.00 mg/kg, 29.40±0.00 mg/kg), Schilbe mystus from Ikot Otu had the highest concentration of Cd (0.06±0.47 mg/kg). Mormyrus rume from Itu Head Bridge and Ikot Iwatt had the highest concentration of Ni (19.19±0.33 mg/kg) and Pb (0.431±0.92 mg/kg), similarly Synodontis Schall from Ikot Otu and Ikot Iwatt had the highest concentration of Cu (21.62±0.03 mg/kg) and Cd (0.09±0.51 mg/kg) respectively. The results of the concentration of heavy metal in this study were below the permissible limits recommended by the National Environment Standards and Regulations Enforcement Agency, the European Commission, and the Joint Expert Committee of the Food and Agricultural Organization/World Health Organization FAO/WHO for food. This implies that fish from the cross-river system contained low concentrations of heavy metals. However, there is a need for research to assess the health impacts of these heavy metals in fish and the potential for transfer to humans. Also, there is a need for routine heavy metal monitoring programmes in fish along the Cross River System to help in the execution of heavy metals regulatory standards by the government and relevant environmental health management agencies.